Implementasi Akad Mudharabah Mutlaqah Dalam Produk Tabah Terhadap Minat Nasabah di KSPPS BMT NU Cabang Pragaan - Supriyadi Supriyadi; Moh Zaki (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2024)
BMT NU East Java Pragaan Branch, has a wide range of savings products. The annual increase in 2020 is that 800 customers have joined the Mudharabah Savings Product. (TABAH), In 2021 there are 1400 customers who have joined the Mudharabah Savings product. (TABAH), In 2022 there are 1700 customers who have joined the Savings product (TABAH), this TABAH product uses Akad Mudharabah Mutlaqah. The problems raised in this planiet are: 1. How is the Process of Implementing Akad Mudharabah mutlaqah in TABAH Products to Customer at KSPPS BMT NU East Java Pragaan Branch 2. How is the marketing strategy carried out by KSPPS BMT NU East Java Pragaan Branch on Tabah products. The methods used are method interview, observation, and documentation. From this method then researchers process and analyze to obtain data or information. The subject of this study was taken from the head of the BMT NU branch, the Savings Sector, the Administration Field. For the validity of the data, researchers use tricoagulation by comparing observational data and interview results. The implementation of the Mutlaqah mudharabah contract is contained in the terms and flows in the management mechanism. The strategy used is: 4p(Product, Price, Place, Promotion). Where this steadfast product is different from other products so it is very interesting to research.